Tacrolimus and mycophenolate mofetil in corticosteroid-resistant hepatitis secondary to tislelizumab: a case report - Jiang, Chang; Guo, Shanxian (Frontiers in Oncology, 2025)
Tislelizumab is a monoclonal antibody with high binding affinity for programmed death-1 (PD-1) receptors. In patients with extensive-stage small-cell lung cancer (ES-SCLC), the first-line use of tislelizumab combined with chemotherapy has shown significant efficacy. However, with the widespread use of PD-1 inhibitors, there are increasing reports of immune-related adverse events (irAEs) in clinical practice, with immune-related hepatitis (IRH) being particularly common. This article reports a case of an ES-SCLC patient (cT3N3M0 cStage IIIB) who developed corticosteroid-resistant hepatitis and recovered through dual immunosuppressant therapy. The patient was a 67-year-old male, diagnosed with ES-SCLC, who received a combination therapy of etoposide, cisplatin, and tislelizumab. Three weeks after the fourth treatment cycle, the patient experienced symptoms, such as decreased appetite, itching, yellow urine, and jaundice, and was diagnosed with IRH, manifested as “Grade 3 total bilirubin increase,” “Grade 3 alanine transaminase increase,” and “Grade 3 aspartate transaminase increase.” Despite intravenous injection of methylprednisolone (MP) 100 mg/day (2 mg/kg) and oral administration of mycophenolate mofetil (MMF) 1 g twice daily, liver function continued to be impaired. In this context, tacrolimus (TAC) (5 mg, twice daily) was added to the therapy, and the IRH level was reduced from Grade 3 to normal. Subsequently, TAC and MMF were gradually reduced and eventually discontinued. Unfortunately, after discontinuing immunosuppressants, IRH recurred. Although the patient still responded to TAC combined with MMF, liver function recovery took a longer time. Due to persistent liver dysfunction, the patient failed to receive second-line chemotherapy and ultimately passed away due to disease progression. Through this case, we hope to emphasize the importance of reasonably extending the use of immunosuppressants to avoid the recurrence of IRH and reduce the premature discontinuation of immunosuppressants. Besides, when tumor progression and IRH recurrence occur simultaneously, providing effective immunosuppressive therapy and reasonably arranging systemic anti-tumor therapy may bring clinical benefits to patients.